Recent Progress on Chemical Production From Non-food Renewable Feedstocks Using Corynebacterium glutamicum - Zhang, Bin; Jiang, Yan; Li, Zhimin; Wang, Fei; Wu, Xiao-Yu (Frontiers in Bioengineering and Biotechnology, 2020)
Abstract: Due to the non-renewable character of fossil energy, microbial fermentation was considered as a sustainable approach for chemicals production by using glucose, xylose, menthol, and other carbon substrates. Among them, xylose, methanol, arabinose, glycerol, and other alternative feedstocks were identified as non-food powerful sustainable carbon substrates that is capable of vigorous development for microbe-based bioproduction. Corynebacterium glutamicum is a model gram-positive bacterium that has been extensively engineered to produce amino acids and other chemicals. Recently, to reduce the production costs and avoid compete food with humans, C. glutamicum to has also been exceedingly engineered to broaden its substrate spectrum. Strengthening endogenous metabolic pathways or assembling heterologous metabolic pathways enables C. glutamicum rapidly catabolizing multitude of carbon sources. This review summarized the recent progress on the metabolic engineering modulation in C. glutamicum towards broad substrate spectrum and chemicals production. In addition, utilization of complex hybrid carbon source is also discussed.